2020
DOI: 10.1039/c9cp06207f
|View full text |Cite
|
Sign up to set email alerts
|

Non-humidified fuel cells using a deep eutectic solvent (DES) as the electrolyte within a polymer electrolyte membrane (PEM): the effect of water and counterions

Abstract: In this research, deep eutectic solvents (DESs) were prepared and employed as electrolyte in Nafion membranes for PEM fuel cell application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…We suggest that the enhancements of the tensile strength and Young's modulus and the reduction of fracture strain for DES-gels may relate to the growing viscosity when more salts are introduced (Figure 1b) [31]. Additionally, previous researches demonstrated that the viscosity of DES increases with decreasing temperature [32]. Thus, the mechanical properties of DES-gels may be also affected by temperature.…”
Section: Des-gels Synthesis and Propertiesmentioning
confidence: 83%
“…We suggest that the enhancements of the tensile strength and Young's modulus and the reduction of fracture strain for DES-gels may relate to the growing viscosity when more salts are introduced (Figure 1b) [31]. Additionally, previous researches demonstrated that the viscosity of DES increases with decreasing temperature [32]. Thus, the mechanical properties of DES-gels may be also affected by temperature.…”
Section: Des-gels Synthesis and Propertiesmentioning
confidence: 83%
“…DES composed of sodium salts (NaCl, sodium bromide NaBr, sodium iodide NaI, sodium nitrate NaNO3) as the HBA with EG or NMAA as the HBD were introduced and preliminarily suggested for application in supercapacitors and fuel cells. 98,[183][184][185] For the systems based on sodium halides, density and viscosity were in the ranges 1.12-1.50 g•cm −3 and 7.35-81.23 mPa•s in the temperature interval 20-60 °C, and increased in the order NaCl < NaBr < NaI (note however that different molar ratio were used for the three DESs, 1:16, 1:6 and 1:4 for NaCl, NaBr and NaI, respectively) (Table 4). 184 For the same salt, e.g.…”
Section: Type IV Dess Composed Of Sodium/potassium Salts and Hbdsmentioning
confidence: 99%
“…For instance the addition of 15 wt% water in NaBr:EG at molar ratio 1:10 caused about a 173% drop in DES viscosity at 20 °C compared to the pristine DES, while the presence of 5, 10 and 15 wt% water increased the proton conductivity at 100 °C up to 17%, 31% and 36%, respectively. 185 As far as potassium is concerned, potassium carbonate K2CO3 was used in combination to G and EG. 186 Gbased DESs showed very high viscosities, with values of 28, 18 and 5.5 Pa s at molar ratio 1:4, 1:5 and 1:6 (Table 4).…”
Section: Type IV Dess Composed Of Sodium/potassium Salts and Hbdsmentioning
confidence: 99%
“…Given the current environmental challenges associated with fossil fuels, fuel cell technology has been introduced as a promising, cleaner, high energy density, and more efficient power generation system [2,8,9]. The first fuel cell to operate with hydrogen and oxygen was developed about 150 years ago by Sir William Grove and was then further studied by developing many other sorts of fuel cells within the 19th century [8,10]. Lately, polymer electrolyte membrane (PEM) fuel cells, which directly convert the chemical energy of hydrogen into electrical energy, were predominantly developed as the most common commercial fuel cell [11,12].…”
Section: Introductionmentioning
confidence: 99%